Theory of world security - Booth, Ken 1943- (Cambridge University Press, 2007)
What is real? What can we know? How might we act? This book sets out to answer these fundamental philosophical questions in a radical and original theory of security for our times. Arguing that the concept of security in world politics has long been imprisoned by conservative thinking, Ken Booth explores security as a precious instrumental value which gives individuals and groups the opportunity to pursue the invention of humanity rather than live determined and diminished lives. Booth suggests that human society globally is facing a set of converging historical crises. He looks to critical social theory and radical international theory to develop a comprehensive framework for understanding the historical challenges facing global business-as-usual and for planning to reconstruct a more cosmopolitan future. Theory of World Security is a challenge both to well-established ways of thinking about security and alternative approaches within critical security studies
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Philosophie; Security, International / Philosophy; World politics / 1989-; Sicherheitspolitik